1996
DOI: 10.1002/(sici)1097-0231(19960331)10:5<529::aid-rcm522>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2,6-Dihydroxyacetophenone for Analysis of Fragile Peptides, Disulphide Bonding and Small Proteins by Matrix-assisted Laser Desorption/Ionization

Abstract: Several peptides were shown to undergo fragmentation during matrix-assisted laser desorption/ionization time-of-flight mass spectrometry to a degree which complicated their analysis using alpha-cyano-4-hydroxycinnamic acid (CHCA) as a matrix, even at threshold laser irradiance. These peptides included synthetic peptides, peptides isolated from viral proteins and a phosphopeptide from beta-casein (residues 33-48). The excessive fragmentation occurred usually as a post-source phenomenon; however, in-source fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…However, no h t H + was detected for the phosphohistidine-containing peptides in positive-ion MALDI analysis, when CHCA or 2,5-dihydroxy-benzoic acid (DHB) were used as matrices. It has been reported that a mixture comprising of 2,6-dihydroxy-acetophenone (DHAP) and di-ammonium hydrogen citrate (DAHC) is a suitable matrix for the MALDI analysis of a series of chemically labile compounds (Gorman et al, 1996). Using this "cooler" matrix, we eventually succeeded in obtaining molecular ions of the phosphorylated histidine-containing peptides in reflectron mode, although abundant ions were still detected due to dephosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, no h t H + was detected for the phosphohistidine-containing peptides in positive-ion MALDI analysis, when CHCA or 2,5-dihydroxy-benzoic acid (DHB) were used as matrices. It has been reported that a mixture comprising of 2,6-dihydroxy-acetophenone (DHAP) and di-ammonium hydrogen citrate (DAHC) is a suitable matrix for the MALDI analysis of a series of chemically labile compounds (Gorman et al, 1996). Using this "cooler" matrix, we eventually succeeded in obtaining molecular ions of the phosphorylated histidine-containing peptides in reflectron mode, although abundant ions were still detected due to dephosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of DHAP, DHB, and CHCA Matrices-We used DHAP as the matrix because it is a "cooler" matrix than CHCA (30) and resulted in less PSD at the relatively high fixed laser energy (350 J/pulse) of our MALDI Q-TOF instrument. Fig.…”
Section: Phosphopeptide Methylation and Detection By Maldi Q-tof Msmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry was performed with a Bruker Reflex mass spectrometer (Bruker-Franzen Analytik, Bremen, Germany) operated exclusively in the reflectron mode as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…Peptides were diluted in 30% (v/v) aqueous acetonitrile containing 0.1% (v/v) trifluoracetic acid and 2 l of a matrix comprised of 2,6-dihydroxyacetophenone containing diammonium hydrogen citrate (25) prior to deposition of 0.5-1 l onto a stainless steel target. Reduction was achieved by adding diammonium hydrogen citrate to the diluted peptide solutions to a final concentration of 0.2 M followed by TCEP to a final concentration of 10 mM and incubation of the mixture for 20 min at 65°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation